ChemInform Abstract: CuI Catalyzed Sulfonylation of Organozinc Reagents with Sulfonyl Halides. Issue 48 (2nd December 2014) - Fu, Ying; Zhu, Wenbo; Zhao, Xingling; Huegel, Helmut; Wu, Zhouqiang; Su, Yuhu; Du, Zhengyin; Huang, Danfeng; Hu, Yulai
Abstract The title reaction provides access to a series of alkyl, aryl and hetaryl sulfones (III) and (V) bearing various kinds of functional groups.